403 Using ruminally protected and unprotected Saccharomyces cerevisiae fermentation products as alternatives to antibiotics in finishing beef steers: growth performance and antimicrobial resistance. (5th December 2019) - Shen, YiZhao; Ran, Tao; Saleem, Atef; Narveaz, Claudia; Gomaa, Walaa; Yang, Wenzhu; Davedow, Taylor; Yoon, Ilkyu; McAllister, Tim A
Abstract: The objectives of this study were to assess the effects of Saccharomyces cerevisiae fermentation products (SCFP; NaturSafe® and Original XPC™, Diamond V) on growth performance and antimicrobial resistance in beef steers. Ninety Angus steers (initial BW=533±9.8 kg) were assigned to a randomized complete design with 6 treatments: 1) control (10% barley silage and 90% barley concentrate, DM basis), 2–4) control diet with 12, 15 and 18 g/d NaturSafe, 5) control diet with 8 g/d encapsulated XPC (eXPC), and 6) control diet with antibiotics (ANT; 330 mg/d monensin and 110 mg/d tylosin). Data were analyzed using the MIXED procedure of SAS with the fixed effect of treatment and random effect of steers. Though the final BW (715 kg) and DMI (12.0 kg/d) were not affected by treatments, average daily gain tended (P < 0.10) to be greater in steers supplemented with eXPC compared with control (1.80 vs. 1.62 kg/d) with a trend (P < 0.09) for a linear increase in gain: feed with increasing NaturSafe. The proportion of total abscessed liver did not differ among treatments (58.9%), but the proportion of severely abscessed liver tended (P < 0.10) to be lower in cattle supplemented with 15 and 18 g NaturSafe/d, eXPC and antibiotics (20.0, 20.0, 20.0 and 6.7 vs. 53.3%). The percentage of erythromycin resistant and erythromycin + tetracycline resistant Enterococci increased (P < 0.05) in steers receiving antibiotics compared with control and SCFP group (34.57 vs. 4.28 and 6.88%), while no difference was observed between control and SCFP groups. These results indicate that NaturSafe and eXPC were beneficial in improving the growth performance by increasing average daily gain and feed efficiency. Both NaturSafe and eXPC could potentially act as alternatives to growth promoting antibiotics.